A mixed methods study exploring barriers and facilitators to secondary-care nurses discussing smoking cessation with patients: phase 1 of the Think Quit Study - Megan Elliott; Katy-May Price; Rachael M. Hewitt; Nicky Knowles; Siva Ganesh; Jessica Baillie; Lauren Jones (BMC Nursing)
Abstract Background Tobacco smokers have increased hospital admissions and experience more health complications compared to those who do not smoke. As such, admission to hospital presents an opportunity for intervention. Nurses play a fundamental role in health promotion, and are well positioned to implement and deliver smoking cessation interventions, but barriers exist. The present study aimed to systematically identify barriers and facilitators experienced by nurses when undertaking two target behaviours; (1) discussing smoking with patients and (2) referring them to smoking cessation services. Methods A convergent mixed methods study was conducted with secondary care nurses in a University Health Board in South Wales. Informed by the Theoretical Domains Framework (TDF) and the COM-B model of behaviour, data were collected using a self-administered anonymised survey and a series of focus groups and interviews that explored experiences of nurses and determinants of the target behaviours. Descriptive and inferential statistics were used to analyse survey responses and explore relationships between nurse characteristics and behavioural determinants. Deductive framework analysis was used to code qualitative data to TDF domains. Results Survey responses were received from 110 nurses working across 13 speciality areas. Nurse respondents perceived the target behaviours to be very important, and reported frequently undertaking the target behaviours. From the TDF, skills, social influences, environmental context and resources and reinforcement domains had the lowest scores, indicating greater perceived barriers in these areas. Twenty-one nurses participated in focus groups (n = 5) and interviews (n = 2). Factors influencing the target behaviours were identified for 10 of 14 TDF domains. Facilitators included seeing these behaviours as consistent with their role and utilising the presence of prompts in the environment, whilst barriers included lack of and inconsistent referral methods, competing priorities and patient resistance. Conclusions Nurses recognise the importance of their role to discuss smoking but have limited knowledge of local smoking cessation services and experience barriers in their workspace. Reducing barriers to discussing smoking and referring patients will facilitate nurses to support their patients to achieve the best health outcomes through quitting smoking.